The International Politics of Migration Interstate Relations and the Peoples Who Cross Borders - Tadokoro, Masayuki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This book discusses the impact of cross-border migration on the relationships between sovereign states. While there is already a vast amount of literature on immigration, it often focuses on issues such as human rights, citizenship, and social integration, reflecting the contemporary interests of Western countries. However, as long as the most fundamental norm of international politics remains the mutual recognition of exclusive jurisdictional rights over territory by sovereign states, people crossing borders pose various challenges to this system of sovereign states. It is this awareness of the issue that makes this book unique. This book examines the implications of the movement of people across national borders both for the state and for international politics. From the standpoint of international politics, the focus of the examination is the international political meaning of the transnational phenomenon of the movement of people. This is an interest that extends from the study of international political economy, which questions the significance for international politics of the transnational phenomena of international trade and international finance. This is an Open Access book.
Introduction: International Politics of Migration The Issues and Basic Facts -- Chapter 1 Policy of Population Movement and Foreign Relations -- Chapter 2 The Limits of Policy$1 (BIrregular Population Movement -- Chapter 3 The State and its Membership -- Chapter 4 Inclusion and Reproduction of Members -- Chapter 5 Overseas Compatriots and the State -- Chapter 6 International Population Movement: What it Means for Japan -- Addendum -- Citations and Reference Works -- Index -- Index of Names and Places.s
Keywords: Emigration and immigration -- Government policy; International relations; Migration Policy; International Relations